Pengembangan Modul Bimbingan Karier Berbasis Pendekatan Karakter Kinerja Di SMA - Samy Purnamy Drachman; Rufi'i; Muhammad Muhyi (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2020)
The career development program aimed to guide students to secure employment. This study contributed to the discussion by developing a career development module with character development as guidance of students’ decision making. Sixty students participated in this study, analyzed with a quantitative descriptive method. This study revealed that the design validation was 92%, with 4,6, as good. Content validation was 96% or the average of 4,8 (good). Instrument Validation was also good. Partner validation was 92%, or 4,6 (good). After designing, this study applied the development test. The result revealed the test of a small group to be 88,5%, middle group to be 91,8%, and a big group to be 93,1%. This study concluded the career development module was good for field application and offered precious information to the school counselor, counseling supervisor, and the counselor herself.